السياسة الضريبية في العراق ومتطلبات الإصلاح - بسمان عبدالمنعم جمال الدين النوري; سراء سالم داؤد الجرجوسي (PROSPECTIVE RESEARCHES, 2023)
A successful and effective tax policy relies on a set of key rules and adheres to them free of guess work and haphazardness therefore, a tax system must be developed in which there is clarity in sitting priorities for goals that are related to the economic, social, and financial reality and most importantly an appropriate and coherent combination between tax objectives and other economic policies. The research aims to analyze direct and indirect tax revenues, with indicating the size of each of them during the study period, and identifying obstacles to maximizing taxes, whether direct or indirect, and the tax revenue data in Iraq from (1995-2019) has been analyzed. The study reached the following conclusion, and the most important of which was that there was no effective direction and planning, coordination and suitability between tax policy and economic and financial policy, leading to the success of the tax policy, but rather the main dependence on oil revenues, and neglecting the role of tax revenues in the budget. The study recommends an attempt to change and amend the tax structure by creating new taxes such as value-added tax and pollution tax, which represent a very abundant outcome of tax revenues in light of the economic conditions in Iraq, in addition to the return of the customs tax because the Iraqi economy depends mainly on revenues and for all goods and services.